2020
DOI: 10.3390/nu12113378
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in 2020: An Old Pro-Hormone with Potential Effects beyond Mineral Metabolism

Abstract: Vitamin D is not a vitamin but a pro-hormone. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Vitamin C (ascorbic acid) cannot be synthesized by the human organism, but it is found in many fruits and vegetables [ 17 , 18 , 19 ] and is used as a supplement, alone or in combination with other vitamins and minerals [ 20 ]. Vitamin D exists in two forms: vitamin D2 (found in plants) and vitamin D3 (found in food and synthesized in the skin under sunlight ultraviolet-B ray exposure), both of which are available in dietary supplements [ 21 , 22 ]. An indoor lifestyle, sun avoidance for health or cultural reasons, and a modern diet based on highly processed food are significant contributors to the evolution of global vitamin D deficiency [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C (ascorbic acid) cannot be synthesized by the human organism, but it is found in many fruits and vegetables [ 17 , 18 , 19 ] and is used as a supplement, alone or in combination with other vitamins and minerals [ 20 ]. Vitamin D exists in two forms: vitamin D2 (found in plants) and vitamin D3 (found in food and synthesized in the skin under sunlight ultraviolet-B ray exposure), both of which are available in dietary supplements [ 21 , 22 ]. An indoor lifestyle, sun avoidance for health or cultural reasons, and a modern diet based on highly processed food are significant contributors to the evolution of global vitamin D deficiency [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal, gastric, duodenal, and rectal epithelial cells have been shown to express the ACE2 receptor; in fact, plasma cells and lymphocytes indicating the activation of immune cells of the mucosa have been observed in the lamina propria of these organs [ 8 ]. Vitamin D (VD) is a fat-soluble vitamin with a pleiotropic effect on many tissues and organs, and is today considered a pro-hormone [ 9 ]. Among the most important biological roles of VD are controlling bone rearrangement, having an effect on both osteoblasts and osteoclasts, and absorbing calcium and phosphorus intestinally, facilitating their homeostasis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D (VD) is a fat-soluble vitamin with a pleiotropic effect on many tissues and organs, and is today considered a pro-hormone [ 9 ]. Among the most important biological roles of VD are controlling bone rearrangement, having an effect on both osteoblasts and osteoclasts, and absorbing calcium and phosphorus intestinally, facilitating their homeostasis [ 9 , 10 ]. Nevertheless, many additional roles have been described for VD, from drug metabolism to the control of the immune response [ 1 , 9 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D was first discovered in the early 20th century and was considered to be a fat-soluble vitamin. Recent studies have demonstrated that vitamin D plays numerous roles as a prohormone in the human body [ 1 ], and is mainly involved in bone and calcium metabolism [ 2 3 ]. Vitamin D is produced in the skin through exposure to adequate sunlight, or is ingested in the form of vitamin D 2 (ergocalciferol) and vitamin D 3 through food.…”
Section: Introductionmentioning
confidence: 99%